A reconciliação entre ética e política na hermenêutica filosófica enquanto filosofia da finitude - Quirino, Regio Hermilton Ribeiro (2023)
In this work the elaboration of reconciliation between ethics and politics is advocated from the perspective of Hans-Georg Gadamer's Hermeneutics as a philosophy of finitude. Recognizing that these themes, ethics, and politics are present in Gadamer's thought, albeit in a dispersed rather than concise form, the focus here is on reconciliation. This new reconciliation between both is established on a new foundation compared to previous periods: finitude, which simultaneously encompasses language and history. The construction of this path traces its roots back to ancient Greek thought, through the modern technical-scientific rationality, and arrives at the present moment. The objective is to present the reconciliation between ethics and politics in contemporary times and its potential normative implications in the current positive legal system, aiming to broaden the concepts and expressiveness of the contemporary world. This understanding of the relationship between language and the world is derived from Gadamer's philosophy. Consequently, concepts like the hermeneutical subject and the hermeneutical state emerge as theoretical-reflexive constructs within the realm of hermeneutical rationality and its practical philosophical dimension, all in an attempt to articulate a coherent unity of meaning that ensures the full exercise of human solidarity.